2005
DOI: 10.1111/j.1445-2197.2005.03512.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic chondrolysis of the hip: medium‐ to long‐term results

Abstract: Circumferential capsulectomy with aggressive mobilization of the hip can correct the deformities associated with this condition, although long-term results are uniformly disappointing with regard to return of hip joint motion in cases of late presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…Korula y col publicaron el mayor número de casos tratados quirúrgicamente (21 casos). Realizaron una capsulectomía subtotal cuando fallaba el tratamiento conservador, con mejoría significativa del movimiento de la articulación 11 . La artroplastia de sustitución por debajo de los 20 años de edad es controvertida y no se recomienda actualmente 2 .…”
Section: Discussionunclassified
“…Korula y col publicaron el mayor número de casos tratados quirúrgicamente (21 casos). Realizaron una capsulectomía subtotal cuando fallaba el tratamiento conservador, con mejoría significativa del movimiento de la articulación 11 . La artroplastia de sustitución por debajo de los 20 años de edad es controvertida y no se recomienda actualmente 2 .…”
Section: Discussionunclassified
“…The radiographic findings are characteristic. The radiological hallmark of this condition has been described as symmetric narrowing of the hip joint space (<3 mm), without frank osteophyte formation, in conjunction with periarticular osteopenia 2,3,5 . A variety of possible radiographic findings without significant pathological related has been reported 2,3,5 .…”
Section: Discussionmentioning
confidence: 99%
“…ICH is characterized by the rapidly progressive destruction of articular cartilage in the hip joint, in the absence of known aetiologies [1][2][3][4][5] . The diagnosis is made by exclusion of other hip diseases with similar symptoms and signs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 They also reported restoration of the joint space on radiographs. 19 Other authors however reported clinical and radiological progression of the disease following similar surgical procedures 39,40,43 and early clinical improvement with radiological deterioration and no long-term benefit. 20 In all our cases the pain was improved following surgery, with four out of five cases pain-free.…”
Section: Outcomementioning
confidence: 99%